Testamentetokak, Hiobib aglangit, Salomoblo imgerusersoanga tikkilugit [electronic resource]. - Morhardt, J. L.; Erdmann, Friedrich, 1810-1873. ([Stolpen, Germany? : s.n.], 1871)
Tranlsation runs from Job to the Song of Songs. "The translation of Psalms and Proverbs is a revision of the translation made by J.L. Morhardt; Job, Ecclesiastes, and the Song of Solomon were translated by F. Erdmann"--Canadiana, 1867-1900. "Printed for the British and Foreign Bible Society in London, for the use of the Moravian mission in Labrador." Electronic reproduction. Mode of access: Internet. 44